Perspectives on national rights in Vietnam at the beginning of the 20th century - Hien, Do Thi (Research Journal in Advanced Humanities, 2024)
Since the end of the 19th century, capitalism transitioned from free competition to imperialism. Imperialist capitalist countries intensified the exploitation of their laboring populations internally and subjected colonized peoples to invasion and oppression externally. Tensions between colonized peoples and colonialism grew increasingly intense, with strong resistance movements against invasion occurring in colonial countries. By the early 20th century, national liberation movements in Asian countries were widespread, significantly influencing the Vietnamese nationalist movement. This article focuses on studying intellectuals’ perspectives on national rights from a bourgeois consciousness, as well as Ho Chi Minh’s views on these rights in the early 20th-century historical context. Based on these perspectives, the author discusses and concludes national rights in Vietnam at the beginning of the 20th century and their significance for the present day.